(untitled) (CIPEEX, 2024)
INTRODUCTION: RESEARCH INTO DEMOGRAPHIC AGING OFTEN HIGHLIGHTS ITS UNFAVORABLE ASPECTS, INCLUDING THE HIGHER INCIDENCE OF CHRONIC CONDITIONS WITH THE POTENTIAL FOR DISABILITY, THE POSSIBLE NEED FOR ASSISTANCE WITH BASIC ACTIVITIES OF DAILY LIVING AND THE INCREASED DEMAND FOR HEALTH SERVICES. DURING THE AGING PROCESS, COMPLAINTS OF COGNITIVE DEFICITS ARE COMMON, AND A RELATIONSHIP HAS BEEN OBSERVED BETWEEN MEMORY COMPLAINTS AND THE APPEARANCE OF DEPRESSIVE SYMPTOMS. PHYSIOTHERAPY PLAYS A SIGNIFICANT ROLE IN PROMOTING A BETTER QUALITY OF LIFE FOR THE ELDERLY POPULATION. WITH AN AGING POPULATION, THERE IS A GROWING NEED FOR LONG-TERM CARE FACILITIES FOR THE ELDERLY. OBJECTIVE: TO DEVELOP KINESIOTHERAPY AND COGNITIVE STIMULATION INTERVENTIONS AIMED AT THE ELDERLY POPULATION LIVING IN A LONG-STAY INSTITUTION FOR THE ELDERLY, IN ORDER TO INVESTIGATE THE EFFECT OF THESE INTERVENTIONS ON THE FUNCTIONAL CAPACITIES AND ACTIVITIES OF DAILY LIVING OF THE ELDERLY. METHODOLOGY: THIS IS AN EXPLORATORY FIELD STUDY OF A PROSPECTIVE AND RETROSPECTIVE COHORT STUDY THAT WILL BE CARRIED OUT AT THE LONG STAY INSTITUTION FOR THE ELDERLY IN CERES-GO, DATA COLLECTION WILL BE CARRIED OUT INDIVIDUALLY, USING THE ANAMNESIS TECHNIQUE. THE RESEARCH WILL INCLUDE THE INITIAL APPLICATION OF THE MINI-MENTAL STATE EXAMINATION, FOLLOWED BY THE IMPLEMENTATION OF EXERCISES OVER 10 PHYSIOTHERAPY SESSIONS BASED ON THE ADAPTED PROTOCOL FOR COMPREHENSIVE HEALTH CARE FOR THE ELDERLY, WHICH HAS ORIENTATION, MEMORY, COMMUNICATION AND FUNCTIONAL INDEPENDENCE AS ITS FOUNDATIONS. AT THE END, THERE WILL BE A SECOND ASSESSMENT WITH THE MINI-MENTAL STATE EXAMINATION FOR COMPARISON. RESULTS: IT IS HOPED THAT THIS RESEARCH WILL REVEAL SOLID EVIDENCE DEMONSTRATING HOW REGULAR PARTICIPATION IN KINESIOTHERAPY ACTIVITIES CAN DELAY OR MITIGATE COGNITIVE DECLINE IN THE ELDERLY. CONCLUSION: THE RESULTS OF THIS RESEARCH MAY EMPHASIZE THAT QUALITY OF LIFE IN THE ELDERLY IS NOT ONLY RELATED TO PHYSICAL FITNESS, BUT ALSO TO MENTAL AND COGNITIVE HEALTH. THEREFORE, INVESTING IN STRATEGIES THAT PROMOTE ACTIVE LIVING, WITH DUE ATTENTION TO KINESIOTHERAPY, HAS POSITIVE IMPLICATIONS FOR SOCIETY AS A WHOLE.